The educational role of the museum - Hooper-Greenhill, Eilean (London ; New York : Routledge, 1999)
- Education, communication and interpretation: towards a critical pedagogy in museums / Eilean Hooper-Greenhill##- Communication in theory and practice / Eilean Hooper-Greenhill##- Learning in art museums: strategies of interpretation / Eilean Hooper-Greenhill##- The museum as a communicator: a semiotic analysis of the Western Australian Museum Aboriginal Gallery, Perth / Robert Hodge, Wilfred D'Souza##- Museum learners as active postmodernists: contextualizing constructivism / Eilean Hooper-Greenhill##- The constructivist museum / George E. Hein##- Teaching yourself to teach with objects / John Hennigar Shuh##- Improving worksheets / Gail Durbin##- Open windows, open doors / Jessica Davis, Howard Gardner##- Museum multicultural education for young learners / Joseph H. Suina##- Children, teenagers and adults in museums: a developmental perspective / Nina Jensen##- Museum-goers: life-styles and learning characteristics / Charles F. Gunther##- Whose museum is it anvwav? Museum education and the community / Jocelyn Dodd##- Learning from learning theory in museums / Eilean Hooper-Greenhill##- Intrinsic motivation in museums: why does one want to learn? / Mihaly Csikszentmihalyi, Kim Hermanson##- Cognitive psychology and interpretation: synthesis and application / Sam H. Ham##- Collaboration: towards a more holistic design process / Hank Grasso, Howard Morrison##- Spatial considerations / Communications Design Team, Royal Ontario Museum##- The exhibition development process / David Dean##- Combating redundancy: writing texts for exhibitions / Margareta Ekarv##- Writing readable text: evaluation of the Ekarv method / Elizabeth Gilmore, Jennifer Sabine##- How old is this text? / James Carter##- Museum text as mediated message / Helen Coxall##- Increased exhibit accessibility through multisensory interaction / Betty Davidson, Candace Lee Heald, George E. Hein##- That those who run may read / Tony Bennett##- Audiences: a curatorial dilemma / Eilean Hooper-Greenhill##
CCS Gent
Includes bibliographical references and index.
boek